Cytosolic Glutamine Synthetase GS1;3 Is Involved in Rice Grain Ripening and Germination - Fujita, Takayuki; Beier, Marcel Pascal; Tabuchi-Kobayashi, Mayumi; Hayatsu, Yoshitaka; Nakamura, Haruka; Umetsu-Ohashi, Toshiko; Sasaki, Kazuhiro; Ishiyama, Keiki; Murozuka, Emiko; Kojima, Mikiko; Sakakibara, Hitoshi; Sawa, Yuki; et al. (Frontiers in Plant Science, 2022)
Ammonium is combined with glutamate to form glutamine. This reaction is catalyzed by glutamine synthetase (GS or GLN). Plants harbor several isoforms of cytosolic GS (GS1). Rice GS1;3 is highly expressed in seeds during grain filling and germination, suggesting a unique role in these processes. This study aimed to investigate the role of GS1;3 for rice growth and yield. Tos17 insertion lines for GS1;3 were isolated, and the nitrogen (N), amino acid, and ammonium contents of GS1;3 mutant grains were compared to wild-type grains. The spatiotemporal expression of GS1;3 and the growth and yield of rice plants were evaluated in hydroponic culture and the paddy field. Additionally, the stable isotope of N was used to trace the foliar N flux during grain filling. Results showed that the loss of GS1;3 retarded seed germination. Seeds of GS1;3 mutants accumulated glutamate but did not show a marked change in the level of phytohormones. The expression of GS1;3 was detected at the beginning of germination, with limited promoter activity in seeds. GS1;3 mutants showed a considerably decreased ripening ratio and decreased N efflux in the 12th leaf blade under N deficient conditions. The β-glucuronidase gene expression under control of the GS1;3 promoter was detected in the vascular tissue and aleurone cell layer of developing grains. These data suggest unique physiological roles of GS1;3 in the early stage of seed germination and grain filling under N deficient conditions in rice.